Historical total and respirable silica dust exposure levels in mines and pottery factories in China - Dosemeci, Mustafa; McLaughlin, Joseph K.; Chen, J.-Q.; Hearl, F.; Chen, R.-G.; McCawley, M.; Wu, Z.; Peng, K.-L.; Chen, A.-L.; Rexing, S. H.; Blot, W. J. (Scandinavian Journal of Work, Environment & Health, 1995)
Historical exposure estimates of total dust and respirable silica were made in a recent nested case-referent study of lung cancer among mine and pottery workers in China. Exposure to total dust and respirable silica was assessed in 20 mines and 9 pottery factories. The average total dust concentration was 7.26 mg·m-3, with a range from 17.68 mg·m-3 in the 1950s to 3.85 mg·m-3 in the 1980s, while the average respirable silica dust was 1.22 mg·m-3, with a range from 3.89 mg·m-3 in the 1950s to 0.43 mg·m-3 in the 1980s. The highest respirable silica dust occurred in the underground mining operations (1.43 mg·m-3), particularly for manual drillers (9.03 mg·m-3). Among all facility types, tungsten mines had the highest respirable silica dust exposure (1.75 mg·m-3), while the lowest exposure occurred in copper-iron mines (0.32 mg·m-3).
Keywords: China; exposure assessment; industrial hygiene measurements; mine; occupational exposure; pottery; retrospective assessment; silica